SurfIP one-stop first-stop intellectual property portal : virtual guide. (Intellectual Property Office of Singapore, 2003)
The guide covers an overview and guided tour of the SurfIP website. SurfIP is an intellectual property portal that offers users comprehensive and integrated IP information and giving them access to databases such as the European Patent Office (EPO), the United Kingdom Patent Office (UKPO), United States Patent Office (USPTO), the World Intellectual Property Organization (WIPO) and more.